Korean Peninsula in the Policy of World Powers in the 21st Century (Economic and Political Thought, 2014)
The article presents the situation on the Korean Peninsula from theperspective of the involved superpowers (China, Japan, Russia and the USA)as well as the two Korean states. Signalling historical conditions for thesuperpowers’ policy towards the Peninsula and demonstrating the diverseinterests of particular states, the author tries to present and explain theirmotivation and makes an attempt to predict future developments. Attentionis also drawn to unprecedented interdependence of the involved parties,which makes it difficult to imagine that the most important problems in theregion can be solved otherwise than by finding a coordinated standpoint andreaching an agreement. The article emphasises the influence of the Koreanstates’ policy on the superpowers’ behaviour and the importance of internalfactors in both Korean states for the pursuit of efficient solutions stabilisingthe situation on the Korean Peninsula.